136k views
1 vote
For given input a the function f outputs a value b to satisfy the following equation:

-3a+6b=a+4b

Write the formula for f(a) in terms of a.

User Angelica
by
4.7k points

2 Answers

0 votes

Answer:

answer with proof

Explanation:

For given input a the function f outputs a value b to satisfy the following equation-example-1
User Justin Cress
by
5.0k points
5 votes

Answer:

Explanation:

-3a-a=4b-6b

-4a=-2b

a=1/2 b

b=2a

f(a)=b=2a

so f(a)=2a

User Lokesh Chowdary
by
4.4k points